صعوبات الداعى تواجها في دعوته في ضوء التفسير الوسيط للقرآن الكريم : Difficulties of dawah Faced by preacher in the light of Tafsir al-Vasit li ‘I-Quran al-Kareem by Muhammad Sayeed al-Tantawi0 (Al-NASR, 2024)
Dr. Sayed Muhammad al-Tantawi one of the prominent scholars. He was late Sheikh of Al-Azhar 1996 AD to 2010 AD .He was   known for his moderate Islamic thought, which combine tradition and modernity. He played a prominent role in reforming Muslim society by mitigating intolerance hatred and ignorance. He was a great preacher and authors. He authored ‘’ Tafsir al-Vasit li ‘I –Quran al-Karim, which is modern Tafsir that contains specific role for proper methodology of dawah .and in this paper the researcher tries to uncover the Difficulties of dawah which are faced by preacher toward other preacher in the light ofTafsir of Dr Tantawi.
Keywords: Difficulties of Dawah faced by preacher; in the Tafsir al-asit li ‘I –Quran al-Karim; Dr. Sayed Muhammad al-Tantawi; Qur’anic Studies